Falling Through the Cracks: the Problem of Granting Software Patents - Eugenia Georgiades (SCRIPT-ed, 2010)
There has been much discussion generated by the open source community with respect to patents. Specifically, the granting of software patents in the US has morphed into a strained and uncontrollable system due to the sheer volume of software patent applications it receives. It has been suggested that software patents are being granted without closer examination as to whether applications meet all of the necessary criteria. This has caused a major rift between software patent owners and the open source community, primarily as a result of software patent owners being granted their patents for claims that technically should be open and free to use in the open source community. The software patents that are being granted fall through the cracks of a patent system that has impacted on the Internet and software space. There have been numerous attempts to redress the imbalance of power that lies with the patent owner by various organisations, one being the Electronic Frontier Foundation (EFF). The EFF established ‘The Patent Busting Project’ in order to combat the validity of software patents that ought to be invalid due to the existence (although mostly undocumented) of prior art in the information and communications technology (ICT) industry. Whether the project has been effective in challenging the validity of software patents is presently uncertain. This paper will discuss and evaluate whether the EFF Patent Busting Project is an effective tool in addressing the conflicts that arise within the patent arena and open source licensing.